Pengaruh Kompetensi Keselamatan Pasien terhadap Aktivitas Keselamatan Pasien dan Penilaian Kinerja Perawat - Prasetyo, Yuda Dwi (Journal of Telenursing (JOTING), 2024)
Patient safety is a crucial issue in healthcare services worldwide. Various safety incidents, including Adverse Events (AEs), Near Misses (NMs), and No Harm Incidents (NHIs), frequently occur and pose serious risks to patients. This study aims to examine the influence of patient safety competence on patient safety activities and nurse performance assessments. The method used is a literature review, which systematically examines relevant journal articles on patient safety and nurse performance. The selected articles were published between 2020 and 2024 and were sourced from electronic databases such as Google Scholar, PubMed, and Springer. Search keywords included "Patient Safety," "Patient Safety Activities," and "Nurse Performance Assessment." The results of the study indicate that nurse competence has a significant influence on patient safety. Additionally, motivation, communication, facilities, and support from hospital management play crucial roles in improving nurse performance. Continuous training programs and nurse empowerment are key steps in minimizing patient safety incidents. In conclusion, patient safety and nurse performance are influenced by a combination of individual and organizational factors. Effective management of competence, motivation, communication, and hospital infrastructure is required to create an environment that supports the consistent application of patient safety standards and reduces the risk of injury. Keywords: Patient Safety, Patient Safety Activities, Nurse Performance Assessment